Fighting Religious Extremism with Faith-Based Entertainment-Education: The Portrayal of isis in Arab Drama - Damanhūrī, Karim ad- (Journal of religion, media and digital culture, 2022)
isis’s media projected the group’s vision of an Islamic utopia upon declaring its so-called Caliphate in 2014. In response, many counter-messaging campaigns have emerged. Although many examine isis’s media and anti-extremism interventions, very few assess faith-based initiatives in Arab countries. Integrating two bodies of scholarly literature on religious and political conversions and entertainment-education, this study explores al-Siham al-Marika, a faith-based Arab drama portraying life under isis. The study uses mixed-methods to analyze the show’s religious underpinnings, the depiction of positive/negative role models, and the portrayals of religious-political conversions. Focusing on spiritual outcomes, the show illustrates cross-cultural differences in conceptualizing rewards and punishments and uses drama to bolster the persuasive power of religious-political conversion narratives. The study concludes with a discussion on the implications of faith-based entertainment-education in combating extremism and its potential role as a catalyst for bridging the perceived schism between religion and popular culture in some Muslim societies.